Challenges for development of meningococcal vaccines in infants and children. (March 2011) - Deasy, Alice; Read, Robert C
Neisseria meningitidis causes significant disease in the form of severe sepsis syndrome or meningococcal meningitis. Owing to the susceptibility of the immune system in early life, the risk of disease after infection is significantly higher in infants. Thus far, vaccines targeted against meningococcal serogroups have struggled to provide lasting protection in young children. Even conjugate vaccines that are now routinely used in the immunization of infants require multiple dosing and the duration of protection has been shown to wane over time and require repeated booster doses. After briefly summarizing the current epidemiology according to age and serogroup, this article will consider the reasons for poor immunogenicity of vaccines in infants and will discuss the relative efficacy of the different vaccine types in this age group. It will then go on to consider strategies for optimizing the protection of infants against meningococcal disease.